2002
DOI: 10.1007/s00417-002-0504-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment by medicine or surgery on intraocular pressure and pulsatile ocular blood flow in normal-pressure glaucoma

Abstract: Patients treated by trabeculectomy and those receiving topical latanoprost and brimonidine had lower IOP and higher POBF following treatment. The betaxolol-treated group, despite a slight decrease in IOP, had a decreased POBF. Lowering IOP by treatment may not necessarily be associated with an increase in POBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
0
17
1
1
Order By: Relevance
“…The POBF, which is based on a measurement of the OPA and recalculated into a POBF value by the Langham OBF system, was found to increase after TE. Similarly, Poinoosawmy et al found an increased POBF 2 weeks after TE using the same device but did not report the OPA [15]. Both studies measured OPA to investigate the long-term change in OBF, which is recognised as an important haemodynamic factor for the pathogenesis of glaucomatous optic neuropathy (for review see [3]).…”
Section: Discussionmentioning
confidence: 99%
“…The POBF, which is based on a measurement of the OPA and recalculated into a POBF value by the Langham OBF system, was found to increase after TE. Similarly, Poinoosawmy et al found an increased POBF 2 weeks after TE using the same device but did not report the OPA [15]. Both studies measured OPA to investigate the long-term change in OBF, which is recognised as an important haemodynamic factor for the pathogenesis of glaucomatous optic neuropathy (for review see [3]).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Georgopoulos et al (2002) reported that POBF amplitude and pulse volume increased 1 week after latanoprost application. Poinoosawmy et al (2002) found that lowering IOP by treatment may not necessarily be associated with an increase in POBF. Sponsel et al (2000) compared the weeklong effects of latanoprost and timolol-XE in normal eyes.…”
Section: Discussionmentioning
confidence: 99%
“…The IOP-lowering effect is explained by increases in uveoscleral outflow [25][26][27] , trabecular outflow facility [28] , or both [29][30][31] . There are also reports of vasodilating activity by travoprost and its ability to increase ocular blood flow to the optic nerve head [32,33] .…”
Section: Discussionmentioning
confidence: 99%